2012
DOI: 10.1111/jfpp.12014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soy Protein Isolate on Physicochemical Properties, Lipid Oxidation and Sensory Quality of Low-Fat Pork Patties Stored in Vacuum, MAP and Frozen State

Abstract: The effect of 2, 5 and 10% soy protein isolate (SPI) addition on selected quality indices of low‐fat pork patties was studied. Patties with SPI showed a higher protein content and lower fat content than the control sample. Water activity was not influenced by SPI addition. The SPI significantly inhibited lipid oxidation in patties during storage. The patties with 10% SPI added showed a detectable level of beany flavor, were more cohesive, harder and less juicy than the other patties. They also received the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
(117 reference statements)
5
18
0
1
Order By: Relevance
“…Figure 6 shows that the addition of mushrooms levels of 40% and higher significantly reduced fat content, while TSP required only substitutions of 20% to have a significant effect on fat content. Pork patties supplemented with 2% to 10% SPI had significantly lower fat contents compared to its all-meat counterpart (Danowska-Oziewicz, 2014). Pork patties supplemented with 2% to 10% SPI had significantly lower fat contents compared to its all-meat counterpart (Danowska-Oziewicz, 2014).…”
Section: Fat Content and Retentionmentioning
confidence: 87%
See 4 more Smart Citations
“…Figure 6 shows that the addition of mushrooms levels of 40% and higher significantly reduced fat content, while TSP required only substitutions of 20% to have a significant effect on fat content. Pork patties supplemented with 2% to 10% SPI had significantly lower fat contents compared to its all-meat counterpart (Danowska-Oziewicz, 2014). Pork patties supplemented with 2% to 10% SPI had significantly lower fat contents compared to its all-meat counterpart (Danowska-Oziewicz, 2014).…”
Section: Fat Content and Retentionmentioning
confidence: 87%
“…Figures 4a and 4b showed that the addition of mushrooms at any concentration significantly reduced the patty's consistency when compared to the all-meat control. 2-5% TSP displayed lower levels of hardness than their all-meat controls (Akesowan, 2010 andKassama, Ngadi, andRaghavan, 2003), pork patties substituted with 2-10% SPI showed increased hardness levels (Danowska-Oziewicz, 2014). 2-5% TSP displayed lower levels of hardness than their all-meat controls (Akesowan, 2010 andKassama, Ngadi, andRaghavan, 2003), pork patties substituted with 2-10% SPI showed increased hardness levels (Danowska-Oziewicz, 2014).…”
Section: Mechanical Testsmentioning
confidence: 94%
See 3 more Smart Citations